Fish consumption of the great cormorant in the area of Hortobágy Fish Farm - Tóth, Norbert; Gyüre, Péter; Juhász, Lajos (Acta Agraria Debreceniensis, 2014)
The cormorant (Phalacrocorax carbo) is a bird species that nests sporadically but in colonies, besides larger fishponds and rivers in Hungary. The number of its individuals has been increasing during the last two decades. The species eats solely fish, therefore it can cause serious depredation of the fish stocks in fishponds of intensive system and after the freezing of the ponds, in larger rivers, which are not yet frozen. The aim of our research is to reveal the damages the birds can cause on the studied areas and the extent of the losses the Hortobágy Fish Farm Co. has to realize. Our studies were carried out between April 2012 and November 2013. During cleaning, the investigation of the crop contents of the birds and their biometric studies were conducted. The results revealed the diverse nutrition base of the species. In the samples, we have determined 300 identified fish individuals; in 289 cases, the exact fish species were determined, too. Although statistical differences were found between the given pond unit and the consuming of the corresponding fish species (P=0.05% beside), this cannot be considered as absolutely certain. Our investigation is of considerable significance in terms of nature preservation and not least, it has substantial financial concerns too. Under the ever harder fish production conditions, the presence and thus the permanent nutrition of the bird affect the fishermen. In favour of the maintaining of the natural ecological balance and the income of the fishers, the elaboration of adequate protective and efficient preventive processes will be necessary in the near future.